Self-Esteem And Adversity Quotient To Increase Learning Independence - Djunaidah, Siti; Matulesy, Andik; Rini , Rr Amanda Pasca (Yayasan Minang Darussalam, 2023)
This study aims to determine whether there is a relationship between Self-Esteem and Advertasy Quetient with learning independence. In the research for class VIII students whose population was 284 students, the number of samples taken was 126 students. From the results of the study, there was a relationship between Self-Esteem and Adversity Quotient with learning independence in Madrasah Tsanawiyah Negri 3 Surabaya students